Analisis Penetapan Titik Kritis Sambaran Petir Pada SUTT 150 kV Koto Panjang – Garuda Sakti Menggunakan Metode Severity Index - Surya Putra; Edy Ervianto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The supply of electrical energy starts with the generation process, then transmitted and then distributed to consumers. It cannot be separated from the disturbances that occur, both internal and external. This study discusses external disturbances in the form of lightning strikes at the SUTT 150 kV Koto Panjang - Garuda Sakti tower using the severity index method. This severity index method produces a tower approach that has the highest level of lightning strike hazard. From the research results, the tower with the most significant severity index value is tower number 1 with a height of 197 m with a severity index value of 13.9 with data on the damage to isolators in the period January - May 2020 totaling three pieces. And the tower with the smallest severity index value is tower number 134 with a height of 35 m and does not have insulator damaged data. From these results, the magnitude of the severity index value of the lightning strike vulnerability on the tower is directly proportional to the damage that occurs in the insulator. Key words: transmission, lightning strike, SUTT 150 kV, severity index, insulator